A high corrosion-resistant nanomaterial sealant and preparation method thereof

By using highly corrosion-resistant nanomaterial sealants, including magnesium-aluminum spinel, hydrotalc, water-based polyurethane and nanosilicon sol during the electroplating process, the oxidative corrosion problem caused by pinholes in the electroplating coating is solved, and better corrosion resistance of the coating and matrix metal protection effect are achieved.

CN117004308BActive Publication Date: 2025-04-15SHENZHEN PASSIVATION TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310979352.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-05
Publication Date
2025-04-15
Estimated Expiration
2043-08-05

AI Technical Summary

Technical Problem

During the electroplating process, pinholes appear on the plating layer, oxygen causes oxidation and corrosion to the base metal through the plating layer, which in turn fails to effectively protect the base metal from corrosion.

Method used

A highly corrosion-resistant nanomaterial sealant is used, which includes magnesium-aluminum spinel, hydrotalcite, aqueous polyurethane, nanosilica sol and silane coupling agent. Through the combined action of these components, the path of external corrosion media to the surface of the protected substrate is extended and pinholes and voids on the surface of the coating are filled.

Benefits of technology

Effectively seal the pinholes and small cracks on the surface of the coating, enhance the corrosion resistance of the coating, protect the matrix metal from corrosion, and improve the adhesion and compatibility of the sealant.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004378800420000011
    Figure BDA0004378800420000011
  • Figure BDA0004378800420000051
    Figure BDA0004378800420000051
  • Figure BDA0004378800420000061
    Figure BDA0004378800420000061
Patent Text Reader

Abstract

The present application discloses a highly corrosion-resistant nanomaterial sealant and a preparation method thereof. A highly corrosion-resistant nanomaterial sealant comprises the following raw materials in parts by weight: 40‑50 parts of waterborne polyurethane, 15‑20 parts of nano-silica sol, 6‑8 parts of silane coupling agent, 4‑7 parts of magnesium aluminum spinel, 3‑5 parts of hydrotalcite, 2‑3 parts of auxiliary agent and 20‑30 parts of deionized water. The preparation method of the highly corrosion-resistant nanomaterial sealant comprises the following steps: S1, mixing the waterborne polyurethane, nano-silica sol, silane coupling agent, magnesium aluminum spinel and hydrotalcite, stirring evenly to obtain a base material; S2, mixing the base material obtained in step S1 with deionized water and auxiliary agent, stirring evenly to obtain the highly corrosion-resistant nanomaterial sealant. The highly corrosion-resistant nanomaterial sealant prepared in the present application has good stability, high adhesion and excellent corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of sealants, and in particular to a highly corrosion-resistant nanomaterial sealant and a preparation method thereof. Background Art

[0002] In various industries, the application of metal materials plays an important role. However, when metal materials are actually used, the materials themselves often corrode, which seriously affects the various mechanical properties of metal products. Electroplating is a process of plating a layer of other metals or alloys on certain metal surfaces using the principle of electrolysis. It is also one of the most widely used metal anti-corrosion methods. However, during the electroplating process, bubbles cannot be expelled due to organic pollution, poor stirring, and uneven surface of the base metal, resulting in pinholes in the coating. As time goes by, oxygen in the air will cause oxidative corrosion to the base metal through the pinholes, and the purpose of the coating to protect the base metal from corrosion is not achieved. Summary of the invention

[0003] In order to solve at least one of the above technical problems, a substance is developed that can seal pinholes, improve the corrosion resistance of the coating, and further protect the base metal from corrosion. The present application provides a highly corrosion-resistant nanomaterial sealant and a preparation method thereof.

[0004] On the one hand, the present application provides a highly corrosion-resistant nanomaterial sealant, which comprises the following components by weight:

[0005] By adopting the above technical solution, by adding magnesium aluminum spinel and hydrotalcite, the path of the external corrosive medium to the surface of the protected substrate can be effectively extended under the joint action of the two, and at the same time, the two can be better combined with waterborne polyurethane and nano-silica sol under the action of silane coupling agent. Hydrotalcite can also load additives due to its unique structure, which can effectively prevent the protected substrate from being eroded. Waterborne polyurethane and nano-silica sol can fill defects such as pinholes and gaps and have good adhesion, so that the sealant has good compatibility with the coating, improve the adhesion of the sealant, form a dense sealing film on the surface of the coating, and enhance the corrosion resistance of the coating.

[0006] Optionally, the average particle size of the nano-silica sol is less than 20 nm.

[0007] By adopting the above technical solution, the nano silica sol has extremely small particle size and high specific surface area, which can better fill and seal the pinholes and fine cracks on the surface of the coating, thereby enhancing the corrosion resistance of the coating.

[0008] Optionally, the silane coupling agent is selected from at least one of 3-methoxypropyltrimethoxysilane, 3-methoxypropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane and aminopropylmethyldiethoxysilane.

[0009] Optionally, the particle size of the magnesium aluminum spinel is 400-500 mesh, and the particle size of the hydrotalcite is 500-600 mesh.

[0010] Optionally, the difference between the particle size of the magnesium aluminum spinel and the particle size of the hydrotalcite is no more than 200 meshes.

[0011] By adopting the above technical scheme, by controlling the particle size of magnesium aluminum spinel and hydrotalcite and the particle size difference between the two, the dispersion effect of the two in the sealant is improved, and it is also convenient for the two to combine with each other to extend the path for the external corrosive medium to reach the surface of the protected substrate. Under the joint action of the two, the substrate can be effectively protected from corrosion and the corrosion resistance of the sealant is enhanced.

[0012] Optionally, the auxiliary agent includes one or more of polysiloxane, polydimethylsiloxane, fatty alcohol polyoxyethylene ether and molybdate.

[0013] By adopting the above technical solution, the auxiliary agent has the effects of a leveling agent and a corrosion inhibitor, so that the sealant has good fluidity, surface flatness and corrosion resistance, and improves the comprehensive performance of the sealant.

[0014] In a second aspect, the present application provides a method for preparing the above-mentioned highly corrosion-resistant nanomaterial sealant, comprising the following steps: S1, mixing the waterborne polyurethane, nano-silica sol, silane coupling agent, magnesium aluminum spinel and hydrotalcite, stirring evenly to obtain a base material;

[0015] S2. Mix the base material obtained in step S1 with deionized water and an auxiliary agent, and stir evenly to obtain the highly corrosion-resistant nanomaterial sealing agent.

[0016] Optionally, step S1 includes the following steps:

[0017] S11, premixing: mixing the waterborne polyurethane, nano silica sol, magnesium aluminum spinel and hydrotalcite, stirring evenly to obtain a premix;

[0018] S12, compounding: mixing the premix obtained in step S11 with the silane coupling agent, and stirring evenly to obtain a base material.

[0019] Optionally, the premix obtained in step S11 is left for 1-2 hours before remixing.

[0020] By adopting the above technical scheme, the preparation method of the sealant is simple and environmentally friendly, the components are evenly mixed, and the premixing operation improves the dispersion effect of magnesium aluminum spinel and hydrotalcite in waterborne polyurethane and nano silica sol and the bonding effect between the four, and leaving the premix for a period of time before remixing is further conducive to the bonding of magnesium aluminum spinel and hydrotalcite, effectively extending the path for the external corrosive medium to reach the surface of the protected substrate. Under the comprehensive effect, the sealant finally prepared has excellent corrosion resistance, good compatibility with the coating, strong adhesion, and good comprehensive performance.

[0021] In summary, the present invention includes at least one of the following beneficial technical effects:

[0022] 1. By adding magnesium aluminum spinel and hydrotalcite, the path of the external corrosive medium to the surface of the protected substrate can be effectively extended under the joint action of the two. At the same time, the two can be better combined with waterborne polyurethane and nano-silica sol under the action of silane coupling agent. Due to its unique structure, hydrotalcite can also load additives, which can effectively prevent the protected substrate from being eroded. Waterborne polyurethane and nano-silica sol can fill defects such as pinholes and gaps and have good adhesion, so that the sealant has good compatibility with the coating, improve the adhesion of the sealant, form a dense sealing film on the surface of the coating, and enhance the corrosion resistance of the coating.

[0023] 2. By controlling the particle size of nano-silica sol and selecting nano-silica sol with extremely small particle size and high specific surface area, the pinholes and fine cracks on the surface of the coating can be better filled and sealed, and the corrosion resistance of the coating can be enhanced. By controlling the particle size of magnesium aluminum spinel and hydrotalcite and the particle size difference between the two, the dispersion effect of the two in the sealant is improved, and it is also convenient for the two to combine with each other to extend the path for the external corrosive medium to reach the surface of the protected substrate, which can effectively protect the substrate from corrosion and enhance the corrosion resistance of the sealant. The auxiliary agent is selected to have the effects of leveling agent and corrosion inhibition, so that the sealant has good fluidity, surface flatness and corrosion resistance, and improves the comprehensive performance of the sealant.

[0024] 3. The preparation method of the sealant of the present application is simple and environmentally friendly. The components are evenly mixed, and the premixing operation improves the dispersion effect of magnesium aluminum spinel and hydrotalcite in waterborne polyurethane and nano silica sol and the bonding effect between the four. The premix is ​​placed for a period of time and then remixed to further facilitate the bonding of magnesium aluminum spinel and hydrotalcite, effectively extending the path for the external corrosive medium to reach the surface of the protected substrate. Under the comprehensive effect, the sealant finally obtained has excellent corrosion resistance, good compatibility with the coating, strong adhesion, and good comprehensive performance. DETAILED DESCRIPTION

[0025] The present application is further described in detail below with reference to the embodiments.

[0026] The present application designs a highly corrosion-resistant nanomaterial sealant, which comprises at least the following components by weight:

[0027] Waterborne polyurethane: 40-50 parts;

[0028] Nano silica sol: 20-30 parts;

[0029] Silane coupling agent: 6-8 parts;

[0030] Magnesium aluminum spinel: 3-5 parts;

[0031] Hydrotalcite: 4-6 parts;

[0032] Additives: 2-3 parts;

[0033] Deionized water: 15-25 parts.

[0034] The highly corrosion-resistant nanomaterial sealant of the present application is prepared by the following method, including the following steps:

[0035] S1, mixing the waterborne polyurethane, nano silica sol, silane coupling agent, magnesium aluminum spinel and hydrotalcite, stirring evenly to obtain a base material;

[0036] S2. Mix the base material obtained in step S1 with deionized water and an auxiliary agent, and stir evenly to obtain the highly corrosion-resistant nanomaterial sealing agent.

[0037] At present, electroplating is one of the most widely used metal anti-corrosion methods. However, in the electroplating process, bubbles cannot be expelled due to factors such as organic pollution, poor stirring, and uneven surface of the base metal, resulting in pinholes in the coating. As time goes by, oxygen in the air will cause oxidative corrosion to the base metal through the pinholes, and then the purpose of protecting the base metal from corrosion by the coating is not achieved. In response to this problem, the present application provides a high corrosion-resistant nanomaterial sealant and a preparation method thereof. By adding magnesium aluminum spinel and hydrotalcite, the path for the external corrosive medium to reach the surface of the protected substrate can be effectively extended under the joint action of the two, and the two can be better combined with water-based polyurethane and nano-silica sol under the action of silane coupling agent. Hydrotalcite, due to its unique structure, can also load auxiliary agents, which can effectively avoid the protection of the substrate from being eroded. Water-based polyurethane and nano-silica sol can fill defects such as pinholes and gaps and have good adhesion, so that the sealant has good compatibility with the coating, improves the adhesion of the sealant, forms a dense closed touch on the surface of the coating, and enhances the corrosion resistance of the coating. Under the comprehensive effect, the sealant finally obtained has excellent corrosion resistance, good compatibility with the coating, strong adhesion and good comprehensive performance. Specific embodiments

[0039] Unless otherwise specified, the raw materials and reagents used in this application were purchased from the market.

[0040] Water-based polyurethane: Oubaodi CUR995;

[0041] Nano-silica sol: Beijing Dekedaojin Technology Co., Ltd.;

[0042] Silane coupling agent: Nanjing Pinning Coupling Agent Co., Ltd.

[0043] Magnesium aluminum spinel: Shanghai Buwei Applied Materials Technology Co., Ltd.;

[0044] Hydrotalcite: Chenghe Technology AC-320;

[0045] Polysiloxane: Shanghai Boer Chemical Reagent Co., Ltd., product number B601699;

[0046] Polydimethylsiloxane: Shanghai Boer Chemical Reagent Co., Ltd., product number B608568;

[0047] Fatty alcohol polyoxyethylene ether: Chengdu 06 Biotechnology Co., Ltd., purity 99%;

[0048] Zinc molybdate: Chengdu Zero Six Biotechnology Co., Ltd., purity 99%.

[0049] Embodiments 1 to 5

[0050] The specific contents of the raw materials in Examples 1-5 are shown in Table 1 below.

[0051] The silane coupling agent used in Examples 1-5 is composed of 3-methoxypropyltrimethoxysilane and 3-methoxypropyltriethoxysilane in a weight ratio of 1:1, and the auxiliary agent is composed of polysiloxane, polydimethylsiloxane, fatty alcohol polyoxyethylene ether and zinc molybdate in a weight ratio of 2:2:3:3.

[0052] Example 1-5 Preparation of a highly corrosion-resistant nanomaterial sealant, comprising the following steps:

[0053] S1, mixing the waterborne polyurethane, nano-silica sol, silane coupling agent, magnesium aluminum spinel and hydrotalcite, stirring at a stirring speed of 800 rpm for 3 min, stirring evenly, to obtain a base material;

[0054] S2. Mix the base material obtained in step S1 with deionized water and an auxiliary agent, stir at a stirring speed of 600 rpm for 5 minutes, and stir evenly to obtain the highly corrosion-resistant nanomaterial sealing agent.

[0055] Table 1: Specific content of raw materials in Examples 1-5

[0056]

[0057] Example 6

[0058] The difference between this embodiment and embodiment 2 is that the average particle size of the nano-silica sol in this embodiment is 30 nm.

[0059] Example 7

[0060] The difference between this embodiment and embodiment 2 is that the particle size of the magnesium aluminum spinel in this embodiment is 400 mesh.

[0061] Example 8

[0062] The difference between this embodiment and embodiment 2 is that the particle size of the hydrotalcite in this embodiment is 600 mesh.

[0063] Example 9

[0064] The difference between this embodiment and embodiment 2 is that step S1 of the preparation method of this embodiment includes the following steps:

[0065] S11, premixing: mixing the waterborne polyurethane, nano-silica sol, magnesium aluminum spinel and hydrotalcite, stirring at a stirring speed of 800 rpm for 5 minutes, stirring evenly, to obtain a premix;

[0066] S12, compounding: the premix obtained in step S11 is mixed with the silane coupling agent, and stirred at a stirring speed of 800 rpm for 3 minutes to obtain a base material.

[0067] Example 10

[0068] The difference between this embodiment and embodiment 9 is that in this embodiment, after step S11, the obtained premix is ​​left to stand for 1 hour before performing the remixing in step S22.

[0069] Comparative Examples 1 to 3

[0070] Comparative Example 1

[0071] The difference between this comparative example and Example 2 is that magnesium aluminum spinel and hydrotalcite are not added in this comparative example.

[0072] Comparative Example 2

[0073] The difference between this comparative example and Example 2 is that this comparative example uses an equal amount of magnesium aluminum spinel instead of hydrotalcite.

[0074] Comparative Example 3

[0075] The difference between this comparative example and Example 2 is that this comparative example uses an equal amount of hydrotalcite instead of magnesium aluminum spinel.

[0076] Experimental testing

[0077] The galvanized nickel alloy carbon steel sheets after passivation and water washing were selected, and two sheets were used as blank examples as blank controls for porosity detection and corrosion resistance detection. The rest were immersed in the sealants prepared in Examples 1-10 and Comparative Examples 1-3 for 30 seconds and then taken out. The excess sealant on the surface of the galvanized nickel alloy carbon steel sheets was blown off with high-pressure air, and then baked at 80-90°C for 40 minutes.

[0078] Test items and test methods

[0079] Adhesion: Tested according to the test method specified in GB / T 9286-1998.

[0080] Porosity: Test porosity according to QB / T 3823-1999 standard. Place test paper soaked in test solution (10g / L potassium ferrocyanide, 20g / L sodium chloride aqueous solution) on the surface of zinc-nickel alloy carbon steel sheet for 5 minutes. If there are pores on the surface, the test solution reacts with the base metal to generate compounds with obvious color difference from the coating, which penetrate into the filter paper and appear as colored spots. Observe the number of spots.

[0081] Corrosion resistance: According to GB / T 10125-2021, the galvanized nickel alloy carbon steel sheet was subjected to a neutral salt spray test, and the time when white spots appeared on the surface of the galvanized nickel alloy carbon steel sheet was recorded.

[0082] Test results

[0083] The test results are shown in Table 2 below.

[0084] Table 2: Test results

[0085]

[0086]

[0087] Results Analysis

[0088] Combined analysis and comparison of the data in Table 1 and Table 2:

[0089] Examples 1-10 and Comparative Examples 1-3 were compared with the blank examples. The porosity of the galvanized nickel alloy carbon steel sheet sealed with the sealant was significantly reduced and the corrosion resistance was significantly enhanced, indicating that the sealants prepared by Examples 1-10 and Comparative Examples 1-3 have excellent corrosion resistance.

[0090] The adhesion of the sealants prepared in Examples 1-10 and Comparative Examples 1-3 is all level 0, the sealants have strong adhesion and good adhesion to the coating.

[0091] Examples 1-3 investigated the effects of the addition amounts of other components except magnesium aluminum spinel and hydrotalcite on the porosity and corrosion resistance of the sealant, wherein the porosity and corrosion resistance of the sealant prepared by Example 2 were better than those of the sealants prepared by Examples 1 and 3, indicating that Example 2 was a preferred example. Using Example 2 as a control, Examples 4 and 5 investigated the effects of the addition amounts of magnesium aluminum spinel and hydrotalcite on the porosity and corrosion resistance of the sealant, wherein the performance of the sealant prepared by Example 2 was relatively better.

[0092] With Example 2 as a control, Example 6 investigates the effect of the average particle size of the nano-silica sol on the porosity and corrosion resistance of the sealant, wherein the porosity and corrosion resistance of the sealant prepared by Example 2 are better than those of the sealant prepared by Example 6, and Example 2 is a preferred example. This indicates that the particle size of the nano-silica sol affects the porosity and corrosion resistance of the sealant, and when the average particle size of the nano-silica sol is less than 20 nm, the prepared sealant has a lower porosity and better corrosion resistance.

[0093] With Example 2 as a control, Examples 7 and 8 investigated the effect of the particle size difference between magnesium aluminum spinel and hydrotalcite on the porosity and corrosion resistance of the sealant, wherein the sealant prepared by Example 2 had a relatively lower porosity and relatively better corrosion resistance. This indicates that when the particle size difference between magnesium aluminum spinel and hydrotalcite does not exceed 200 meshes, the prepared sealant has a lower porosity and better corrosion resistance.

[0094] With Example 2 as a control, Examples 9 and 10 investigate the effects of different preparation conditions on the porosity and corrosion resistance of the sealant, wherein the porosity and corrosion resistance of the sealant prepared by Example 9 are better than those of the sealant prepared by Example 2, and the porosity and corrosion resistance of the sealant prepared by Example 10 are better than those of the sealant prepared by Example 9, indicating that Example 10 is a more preferred embodiment. It is explained that premixing the raw materials improves the dispersion effect of magnesium aluminum spinel and hydrotalcite in waterborne polyurethane and nano-silica sol and the combination effect between the four, and placing the premix for a period of time and then remixing is further conducive to the combination of magnesium aluminum spinel and hydrotalcite. Under the comprehensive effect, the sealant finally obtained has excellent corrosion resistance, strong adhesion and good comprehensive performance.

[0095] Taking Example 2 as a control, Comparative Examples 1-3 investigated the effects on the porosity and corrosion resistance of the sealant without adding magnesium aluminum spinel and hydrotalcite and adding only one of the two. The sealant prepared by Example 2 had a relatively lower porosity and relatively better corrosion resistance. This indicates that under the combined action of magnesium aluminum spinel and hydrotalcite, the porosity of the sealant is significantly reduced and the corrosion resistance is significantly improved.

[0096] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A highly corrosion-resistant nanomaterial sealant, characterized in that: By weight, it includes the following ingredients: 40-50 parts of waterborne polyurethane; 20-30 parts of nano silica sol; Silane coupling agent 6-8 parts; 3-5 parts of magnesium aluminum spinel; 4-6 parts of hydrotalcite; 2-3 parts of additives; 15-25 parts of deionized water; The particle size of the magnesium aluminum spinel is 400-500 mesh, and the particle size of the hydrotalcite is 500-600 mesh.

2. The highly corrosion-resistant nanomaterial sealant according to claim 1, characterized in that: The average particle size of the nano-silica sol is less than 20 nm.

3. The highly corrosion-resistant nanomaterial sealant according to claim 1, characterized in that: The silane coupling agent is selected from at least one of 3-methoxypropyltrimethoxysilane, 3-methoxypropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane and aminopropylmethyldiethoxysilane.

4. The highly corrosion-resistant nanomaterial sealant according to claim 1, characterized in that: The difference between the particle size of the magnesium aluminum spinel and the particle size of the hydrotalcite is no more than 100 meshes.

5. The highly corrosion-resistant nanomaterial sealant according to claim 1, characterized in that: The auxiliary agent includes one or more of polysiloxane, polydimethylsiloxane, fatty alcohol polyoxyethylene ether and molybdate.

6. A method for preparing the highly corrosion-resistant nanomaterial sealant according to claim 1, characterized in that: The following steps are involved: S1, mixing the waterborne polyurethane, nano silica sol, silane coupling agent, magnesium aluminum spinel and hydrotalcite, stirring evenly to obtain a base material; S2. Mix the base material obtained in step S1 with deionized water and an auxiliary agent, and stir evenly to obtain the highly corrosion-resistant nanomaterial sealing agent.

7. The method for preparing the highly corrosion-resistant nanomaterial sealant according to claim 6, characterized in that: The step S1 comprises the following steps: S11, premixing: mixing the waterborne polyurethane, nano silica sol, magnesium aluminum spinel and hydrotalcite, stirring evenly to obtain a premix; S12, compounding: mixing the premix obtained in step S11 with the silane coupling agent, and stirring evenly to obtain a base material.

8. The method for preparing the highly corrosion-resistant nanomaterial sealant according to claim 7, characterized in that: The premix obtained in step S11 is left to stand for 1-2 hours before remixing.

Citation Information

Patent Citations

  • Anticorrosive paint containing ion exchange pigment

    CN110724402A

  • Water-soluble zinc and zinc alloy sealing agent with low sagging and high corrosion resistance

    CN115011226A

  • Corrosion-resistant coating taking secondary aluminum ash as raw material and preparation method of corrosion-resistant coating

    CN116041994A